A revised taxonomy of the ammonoid genus Desmoceras from Japan and southern Sakhalin - Matsumoto, Tatsuro (Proc Jpn Acad Ser B Phys Biol Sci, 2004)
Based on the stratigraphically well sorted material from Japan and southern Sakhalin, the ammonoid species belonging to the genus Desmoceras are classified as follows in ascending order: D. latidorsatum (Michelin) (Middle to mid-Upper Albian), D. dawsoni shikokuense (Yabe and Shimizu) (Upper Albian), D. kossmati Matsumoto (uppermost Albian–Lower Cenomanian), D. japonicum Yabe (uppermost Albian–Cenomanian), and D. ezoanum Matsumoto (mid-Upper Cenomanian–mid-Lower Turonian). D. japonicum can be subdivided into the earlier and later subspecies. D. poronaicum Yabe is a junior synonym of D. japonicum. Despite the scarcely ornamented shell, each taxon can be defined by its own characters.